Metrics in Large-Scale Agile Software Development: A Multivocal Literature Review - Menezes, Renato; Marinho, Marcelo; Sampaio, Suzana (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2024: Anais do XXVII Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2024.28442, 2024)
Software development is widespread across various sectors. As large-scale projects increasingly adopt agile development practices, there arises a need for metrics to enhance team coordination, promote continuous improvement and monitor progress. This discussion focuses on the current state of metrics for large-scale agile software development, outlining the reasons for their adoption and showcasing the achieved results. The analysis involves a comprehensive literature review, exploring grey literature. A catalog of metrics applicable to scalable agile projects is presented, featuring examples such as ‘Velocity’, ‘Business value per effort’, and ‘Defect rate’.